Sealless Production Ultracentrifuge and Its Magnetically Self-Bearing Openable Motors for Purification in Viral Nanotechnology - Emanuel J. Hubmann; Daniel Steinert; Thomas Nussbaumer; Johann W. Kolar (IEEE Access)
Viral nanotechnology enables new possibilities for gene therapies and vaccines. However, the manufacturing of viral vectors lacks a satisfactory production capable method for purification of full capsids. Empty or partially empty capsids need to be removed to avoid immunotoxicity. The state of the art production ultracentrifuges (PUCFs) are limited, especially in rotational speed to approximately 40 krpm by rotary seals, by complexity and virus containment. This prevents PUCFs from widespread use in industry for viral vector production. This article proposes a novel PUCF type with rotational speed potential towards 100 krpm with a hermetically enclosed process chamber without any rotary seals, i.e. a sealless production ultracentrifuge (SL-PUCF) omitting contamination risk. The openable vertical axis self-bearing motors, the novel sealless flow path design and the needed ultra high-speed potential towards 100 krpm pose new technical problems, for which this article proposes and experimentally validates solutions. A SL-PUCF prototype with its vertical axis magnetically self-bearing openable motors (O-SBMs) and openable burst armor (O-BA) is realized, validated and operated as a system. The general working principle of the SL-PUCF system is experimentally validated by whey protein sedimentation. Furthermore, new future smart capability potential of the proposed new SL-PUCF technology suspended and driven by O-SBMs is unveiled as an outlook and examples shown in case studies.